2021
DOI: 10.1111/jocs.15806
|View full text |Cite
|
Sign up to set email alerts
|

Aging as a risk factor for cardiac surgery: Blunted ischemic‐reperfusion stress response?

Abstract: Biological aging is commonly associated with compromised cardiovascular function.In particular, cardiac aging is featured by unfavorable left ventricular remodeling, loss of compliance, and poor contractile reserve. Among possible contributing factors for cardiovascular aging, dampened autophagy response has received much attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…During aging, cardiac and non-cardiac organs change their structure and consequently lose crucial functional components such as the glomeruli of the kidney resulting in functional impairments that may well take place insidiously and unnoticed for a long period [ 4 , 5 , 6 , 7 ]. Various causes are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…During aging, cardiac and non-cardiac organs change their structure and consequently lose crucial functional components such as the glomeruli of the kidney resulting in functional impairments that may well take place insidiously and unnoticed for a long period [ 4 , 5 , 6 , 7 ]. Various causes are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Our study is consistent with a previous study which demonstrated advanced age is a major risk factor for cardiovascular disease [ 16 ]. The mechanisms probably as follows: firstly, aging reduced mitochondrial content and progressively slower stress response to ischemia, contributing to myocardial injury; secondly, autophagy may decrease in aging myocardium as a cellular protective cycling mechanism, leading to cardiac dysfunction and myocardial injury [ 17 , 18 ]. Lee index was widely applied to identify patients at higher risk for perioperative complications or myocardial injury in patients undergoing non-cardiac surgery [ 13 , 19 ].…”
Section: Discussionmentioning
confidence: 99%